Metabolomic study of corticosterone-induced cytotoxicity in PC12 cells by ultra performance liquid chromatography-quadrupole/time-of-flight mass spectrometry. Issue 3 (18th January 2016) - Zhang, Hongye; Zheng, Hua; Zhao, Gan; Tang, Chaoling; Lu, Shiyin; Cheng, Bang; Wu, Fang; Wei, Jinbin; Liang, Yonghong; Ruan, Junxiang; Song, Hui; Su, Zhiheng
Abstract : UPLC-Q/TOF-MS-based cell metabolomics illustrates dysfunction of multiple pathways was involved in the corticosterone-induced cytotoxicity in PC12 cells. Abstract : Glucocorticoids (GCs) have been proved to be an important pathogenic factor of some neuropsychiatric disorders. Usually, a classical injury model based on corticosterone-induced cytotoxicity of differentiated rat pheochromocytoma (PC12) cells was used to stimulate the state of GC damage of hippocampal neurons and investigate its potential mechanisms involved. However, up to now, the mechanism of corticosterone-induced cytotoxicity in PC12 cells was still looking forward to further elucidation. In this work, the metabolomic study of the biochemical changes caused by corticosterone-induced cytotoxicity in differentiated PC12 cells with different corticosterone concentrations was performed for the first time, using the ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF MS). Partial least squares-discriminate analysis (PLS-DA) indicated that metabolic profiles of different corticosterone treatment groups deviated from the control group. A total of fifteen metabolites were characterized as potential biomarkers involved in corticosterone-induced cytotoxicity, which were corresponding to the dysfunctions of five pathways including glycerophospholipid metabolism, sphingolipid metabolism, oxidation of fatty acids, glycerolipid metabolism and sterol lipid metabolism. This study indicated that the rapid and holistic cell metabolomics approach might be a powerful tool to further study the pathogenesis mechanism of corticosterone-induced cytotoxicity in PC12 cells.